The impact of glucocorticoid medication use on hair cortisol and cortisone in older adults: Data from the Irish Longitudinal Study on Ageing. - Kenny, Rose; Feeney, Joanne (My University, 2020)
Research focusing on the hair concentration of cortisol and cortisone has significantly developed over the last two decades and has huge potential to provide relevant insights into stress-related diseases. However it is not clearly understood exactly how glucocorticoid (GC) medications, which are commonly prescribed drugs particularly among older adults, may affect hair cortisol and cortisone levels. The aim of this study was to examine associations of the use of GC medications with hair cortisol and cortisone concentrations in a sample of older adults. Hair samples and data were collected from participants at Wave 3 of The Irish Longitudinal Study of Ageing (TILDA). Results showed that before and after controlling for socio-demographic, health and hair characteristics, the use of systemic GCs was associated with decreased hair cortisone (B= -0.34 95 % CI -0.53, -0.16, p < 0.001). However, the use of local GCs was associated with increased hair cortisol (B = 0.39 95 % CI 0.18, 0.61). Further analysis suggests that the latter finding may be the result of use of topical steroid creams/ointments. These data add to the scant literature on the impact of steroid medication use on hair cortisol and cortisone in non-clinical populations, providing further evidence that future hair GC studies need to consider steroid medication use.
PUBLISHED
Keywords: Hair glucocorticoid; Steroid medication; Older adults; Cortisol; Cortisone; Ageing